ANALISIS KEPATUHAN PERPAJAKAN PELAKU USAHA MIKRO, KECIL, DAN MENENGAH (UMKM) DI INDONESIA: STUDI PADA KOTA BANJARBARU KALIMANTAN SELATAN - Raais Nurizzaman (Jurnal Ilmu Ekonomi dan Bisnis, 2020)
Micro small and medium enterprises (MSMEs) have a very vital role in the growth, development and sustainability of the Indonesian economy, especially in terms of providing large employment opportunities. MSMEs are considered capable of preventing Indonesia from economic storms, able to be a deterrent when there are economic shocks and able to absorb a large number of workers. Tax is an important fiscal instrument for the Indonesian government as a source of state revenue. Therefore, the role and participation of all MSMEs entrepreneurs in Indonesia in paying taxes are indispensable for the development of the Indonesian economy. The objectives of this study are (1) to explain the level of understanding of MSMEs in the City of Banjarbaru to the tax regulations, (2) to explain the low level of tax payment compliance and the reasons for the low level of compliance of MSME taxpayers in Banjarbaru City, South Kalimantan, (3) to analyze the effectiveness of government policies concerning Government Regulation Number 23 of 2018, (4) to analyze the roles that have been carried out by the Government in increasing the compliance of MSMEs in paying taxes in the City of Banjarbaru, South Kalimantan. This research uses a descriptive qualitative approach. The results of this study indicate that MSMEs in the City of Banjarbaru are quite good in understanding taxation regulations, especially related to the Law Number 23 Year 2018. The potential for MSMEs obedience in the City of Banjar Baru, South Kalimantan in paying taxes is still low. The implementation of government regulation No. 23 of 2018 in Banjarbaru City has not been effective because there has not been a significant increase in MSMEs taxpayers. The efforts made by the government in increasing taxpayer compliance are providing good service to the taxpayers. Keywords: MSMEs, Fiscal Policy, Taxpayer Compliance, Government Regulation No. 23 of 2018